2000
DOI: 10.1177/0146167200263005
|View full text |Cite
|
Sign up to set email alerts
|

Race in the Courtroom: Perceptions of Guilt and Dispositional Attributions

Abstract: The present studies compare the judgments of White and Black mock jurors in interracial trials. In Study 1, the defendant’s race did not influence White college students’ decisions but Black students demonstrated ingroup/outgroup bias in their guilt ratings and attributions for the defendant’s behavior. The aversive nature of modern racism suggests that Whites are motivated to appear nonprejudiced when racial issues are salient; therefore, the race salience of a trial summary was manipulated and given to nonco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
269
7
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(295 citation statements)
references
References 27 publications
18
269
7
1
Order By: Relevance
“…Studies that have separately manipulated actor and recipient group membership and found an effect of actor group on adult's third-party punishment have consistently found harsher punishment of out-group actors (7,9,10). Similarly, out-group members receive more second-party punishment for selfish behavior (12,13), and in the context of legal punishment, laboratory and field studies suggest that racial out-group members are judged more harshly (67,68). Thus, there appear to be many contexts in which selfish behavior does not trigger black-sheep or group norm maintenance effects.…”
Section: Recipient Biasmentioning
confidence: 99%
“…Studies that have separately manipulated actor and recipient group membership and found an effect of actor group on adult's third-party punishment have consistently found harsher punishment of out-group actors (7,9,10). Similarly, out-group members receive more second-party punishment for selfish behavior (12,13), and in the context of legal punishment, laboratory and field studies suggest that racial out-group members are judged more harshly (67,68). Thus, there appear to be many contexts in which selfish behavior does not trigger black-sheep or group norm maintenance effects.…”
Section: Recipient Biasmentioning
confidence: 99%
“…3 "No state shall make or enforce any law which shall abridge the privileges or immunities of citizens of the United States; nor shall any state deprive any person of life, liberty, or property, without due process of law; nor deny to any person within its jurisdiction the equal protection of the laws." Amendment XIV, US Constitution 4 Given this difficulty, a number of studies (Devine, et al, 2000;Sommers and Ellsworth, 2000;MacCoun, 1989) have made use of experimental simulations of court cases, most often to understand the behavior of juries. While laboratory studies allow the careful manipulation of the variable of interest, defendant race, sectional studies suffer from a potentially severe omitted variables bias.…”
Section: Introductionmentioning
confidence: 99%
“…However, when race was not made salient, White jurors rated the male defendant as more guilty, violent, and aggressive when he was described as Black than when he was described as White. Thus, making race salient can lead to alterations in behavior that are aligned with social norms about race (Sommers & Ellsworth, 2000. It is worth noting that most of the studies in this meta-analysis that manipulated race salience featured racial majority participants.…”
Section: Contextual Factorsmentioning
confidence: 94%